The physicochemical properties of cocoa butter equivalent produced from lipase-catalyzed palm oil and hydrogenated palm oil via physical fractionation - Mohamad Alwi, Siti Maslina; Lai, Oi Ming (Universiti Putra Malaysia Press, 2019)
Palm oil (PO) and fully hydrogenated palm oil (FHPO) were subjected to enzymatic interesterification using 9.5% of TLIM Lipozyme. The optimum condition for this process occurred at 62.75°C, with reaction time 172.50 minutes with the ratio of 1:1 for palm oil to hydrogenated palm oil respectively. The Palmitoyl-Oleoyl-Stereoyl (POS) yield obtained was approximately 15%. Product was subsequently subjected to a fractionation process at various cooling temperatures and reaction time. At 34°C, POS achieved was at the highest level which was approximately 31% after 12 hours cooling process. The study of physiochemical properties of the Cocoa butter Equivalent (CBE) fat was determined for the purpose of characterization identification. The properties identified were solid fat content, slip melting point (SMP) and iodine value (IV). The IV and SMP values obtained were 44.30 and 29°C respectively. However, CBE produced almost 0% of Solid Fat Content (SFC) at 30°C. Apart from the high yield of POS, the physicochemical characteristics showed significant compatibility with that of CB. In addition, the crystal polymorph of CBE 34 physicochemical characteristics of CBE34 (β'+β) was similar to CBE. Hence, from this study, CBE 34 is recommended for utilization in the confectionery industry as CBE.